Design of a Type C Hospital Isolation Room Based on a Pontoon - Listanti Romdhun (Journal of Interdisciplinary Social Sciences and Humanities, 2026)
The development of adaptable healthcare facilities is essential for Indonesia's coastal and archipelagic regions. This study aims to design an isolation room for a Type C pontoon-based hospital as an innovative solution to improve access to medical services—particularly for infectious disease treatment in remote areas. The methodology includes literature review on isolation room standards, spatial needs analysis based on Ministry of Health regulations, and exploration of pontoon structural characteristics. The findings highlight that isolation rooms on pontoons must address structural stability, negative pressure ventilation, and separation of clean and contaminated circulation paths. The interior design emphasizes space efficiency, user safety, and patient psychological comfort. Applying modular principles further ensures functional flexibility and ease of maintenance. This study is expected to serve as an initial reference for designing floating healthcare facilities that meet medical standards and adapt to geographical and emergency response challenges.